Control Model Analysis of Stunting Risk Determinants in Children - Nurhamidi, Nurhamidi; Fathurrahman, Fathurrahman; Aprianti, Aprianti (Universitas Sari Mulia, 2022)
Background: Stunting in Batola district from the results of monitoring nutritional status from 2013 - 2017 was 47.23% (Info Banua co.id) and Gampa Asahi village was the highest at 50%Aims: This study aims to analyze the risk factors related to the determinants of children under five, mothers and the environment on stunting so that an analysis of the control model can be developedMethods: conducted in 2019 in Sungai Gampa Village, Rantau Badauh District, Materials used Questionnaire, Microtoise, Food Model, Food sample, Food Picture Book Case control, population of all children under five, the technique of sampling the case is the total population, while the control is done by simple random sampling. cases of 50 stunting toddlers and control of 50 normal toddlers. Data analysis, bivariate Chi Square and then with multivariate multiple logistic regression test. Risk factors for stunting Energy intake, protein, infectious diseases, immunization status, history of exclusive breastfeeding, complementary feeding, maternal knowledge, family income, availability of energy and protein foods, parenting, and health services, and environmental healthResult:showed that there were 6 variables related to the incidence of stunting, namely energy and protein intake, history of infectious disease, history of immunization, exclusive breastfeeding, and maternal knowledge with p 0.05. The results of logistic regression showed that there was an effect of exclusive breastfeeding and protein consumption on the incidence of stunting in children under five.Conclusion: There is a relationship between the incidence of stunting with energy and protein intake, history of infectious diseases, history of immunization, exclusive breastfeeding, and maternal knowledge with p 0.05. Based on the results of logistic regression, it shows that there is an effect of exclusive breastfeeding and protein consumption on the incidence of stunting in toddlers.Keywords: Determinants of risk, children under five and mothers, stunting Latar Belakang Stunting di kabupaten Batola dari hasil pemantauan status gizi tahun 2013 – 2017 sebesar 47,23% (Info Banua co.id) dan Desa Gampa Asahi paling tinggi sebesar 50%Tujuan: untuk menganalisis faktor risiko yang berhubungan dengan determinan balita lima, ibu dan lingkungan tentang stunting sehingga dapat dikembangkan analisis model pengendalianMetode: teknik pengambilan sampel kasus adalah populasi total, sedangkan kontrol dilakukan dengan simple random sampling. kasus 50 balita stunting dan kontrol 50 balita normal. Analisis data, bivariat Chi Square kemudian dengan uji regresi logistik berganda multivariat. Faktor ripeer gorup resiko stunting Asupan energi, protein, penyakit menular, status imunisasi, riwayat ASI eksklusif, MPASI, pengetahuan ibu, pendapatan keluarga, ketersediaan makanan berenergi dan protein, pola asuh, dan pelayanan kesehatan, serta kesehatan lingkunganHasil : menunjukkan bahwa terdapat 6 variabel yang berhubungan dengan kejadian stunting yaitu asupan energi dan protein, riwayat penyakit menular, riwayat imunisasi, ASI eksklusif, dan pengetahuan ibu dengan p 0,05. Hasil regresi logistik menunjukkan bahwa ada pengaruh pemberian ASI eksklusif dan konsumsi protein terhadap kejadian stunting pada balita.Simpulan: Ada hubungan antara kejadian stunting dengan asupan energi dan protein, riwayat penyakit menular, riwayat imunisasi, ASI eksklusif, dan pengetahuan ibu dengan p 0,05. Berdasarkan hasil regresi logistik menunjukkan bahwa ada pengaruh pemberian ASI eksklusif dan konsumsi protein terhadap kejadian stunting pada balita. Kata kunci: Balita dan ibu, Determinan risiko, stunting